Implementasi GOOSE (IEC61850) pada Sistem Otomasi Gardu Induk di PLN UPDL Semarang - Said Al Manshury, Muhammad (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
PLN has implemented a lot of Substation Automation Systems (SAS), especially at new substations or extension new bays to conventional substations. The Implementation of SAA cannot be separated from the IEC 61850 protocol which is a standard protocol in SAS. One of the important communications in the IEC 61850 protocol is GOOSE (Generic Object Oriented Substation Event). In GOOSE known GOOSE publisher and GOOSE subscriber. The steps taken in this research are literature review, configuration of GOOSE publisher, GOOSE subscriber, and testing. Based on the results of the testing that have been carried out, it can be concluded that the GOOSE publisher (Scheneider protection IED type P141) can send data to the ethernet network (IEC 61850) and the GOOSE subscriber (Siemens IED controller/BCU type 7SJ642) can receive data from GOOSE publisher. This GOOSE can be implemented on IEDs that both support IEC 61850 even though they are from different brands/manufacturers. For its implementation in the field, GOOSE can be used for interlocking, tripping, blocking and others, where this GOOSE replaces the hardwire. With the implementation of GOOSE on the Substation Automation System, it is expected to reduce the costs and time for hardwire installation.